2017
DOI: 10.1002/wow3.118
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in firms and labour market outcomes

Abstract: This chapter explores how innovation in firms (described as product, process, marketing and organizational innovation) is associated with firm performance and labour market outcomes. For this purpose, it first discusses the evidence to date at the aggregate (i.e. country) level – for as broad a set of economies as possible. Then, it focuses on the firm level based on a group of economies for which data from the Business Environment and Enterprise Performance Surveys (BEEPS) and MENA Enterprise Surveys (MENA ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Human capital plays as the primary factor for the investment abroad (Amit et al, 1998), implying that venture capital is a strict process of establishing the perimeter for choosing the right criteria for investments and what will include into it (Manigart et al, 2007). Many of the new companies that want a part of the global market, now in the process of focusing on human capital as a primary tool, due to the international view on the stuffing process the companies have access to the foreign markets through their stuff, which not only partial to the communication factor but also influenced by their background knowledge and their cultural differences (Richiardi and Postolachi, 2017). All this informational knowledge is one of the new strategies that now implemented in the different companies, who want to succeed in the global markets (Barney, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human capital plays as the primary factor for the investment abroad (Amit et al, 1998), implying that venture capital is a strict process of establishing the perimeter for choosing the right criteria for investments and what will include into it (Manigart et al, 2007). Many of the new companies that want a part of the global market, now in the process of focusing on human capital as a primary tool, due to the international view on the stuffing process the companies have access to the foreign markets through their stuff, which not only partial to the communication factor but also influenced by their background knowledge and their cultural differences (Richiardi and Postolachi, 2017). All this informational knowledge is one of the new strategies that now implemented in the different companies, who want to succeed in the global markets (Barney, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Focusing on product innovation, Zhou, Dekker and Kleinknecht (2011), using longitudinal data from 1988 on also for the Netherlands, conclude that firms with high share of fixed-term contracts perform significantly worse regarding innovation in new products (as opposed to imitative new products). In contrast, research from transition Middle East, North Africa and Sub-Saharan African economies found a higher incidence of temporary employment in more innovative firms (Avenyo 2017;Richiardi and Postolachi 2017).…”
Section: Evidence On the Relation Between Innovation And Job Qualitymentioning
confidence: 97%